The mediating role of the employee relations climate in the relationship between strategic HRM and organizational performance in Chinese banks - Muhammad Ali; Shen Lei; Xiao-Yong Wei (Journal of Innovation & Knowledge (JIK), 2018)
In today's business environment, establishing a positive climate is becoming increasingly important for organizational growth and performance. A positive employee relations climate creates a social atmosphere, which encourages high employee involvement and an employee-centered culture. In response, employees feel comfortable and contribute positively to organizational performance. Given the intensity of competition in the service industry, banks must understand how the employee relations climate and HRM practices affect organizational performance. Banks also need to know which employee relations climate best meets the needs of the organization. Accordingly, this study examined the way the employee relations climate mediates the relationship between strategic HRM practices and organizational performance in Chinese banks. Senior employees of Chinese banks based in Shanghai provided data by responding to a survey questionnaire. CFA and SEM in AMOS 18 were used to test the hypotheses and evaluate measurement validity. The results indicate that strategic HRM has a significant positive relationship with operational performance. In addition, the employee relations climate was found to mediate the relationship between strategic HRM and organizational performance. Cross-sectional data, a restricted target sample (i.e., bank employees), and a restricted target area (i.e., Shanghai) are limitations of this study. In addition, the dimensions of organizational performance were not identified in detail. Finally, the hypothesized relationship was explored only for a specific sector (i.e., the banking sector).
Keywords: D83; 650; Employee relations climate; Organizational performance; Strategic HRM; China; Banks